Future orientation: a construct with implications for adolescent health and wellbeing - Sarah Johnson; Robert W. Blum; Tina L. Cheng (2014)
Abstract Multidisciplinary research has supported a relationship between adolescent future orientation (the ability to set future goals and plans) and positive adolescent health and development outcomes. Many preventive strategies – for example, contracepting, exercising – are based on taking actions in the present to avoid unwanted or negative future consequences. However, research has been hampered by unclear and often divergent conceptualizations of the future orientation construct. The present paper aims to integrate previous conceptual and operational definitions into a conceptual framework that can inform programs and services for youth and efforts to evaluate future orientation as a target for intervention. Recommendations focus on furthering the study of the construct through measurement synthesis as well as studies of the normative development of future orientation. Also suggested is the need to pair environmental intervention strategies with individual level efforts to improve future orientation in order to maximize benefits.